An Impulsive Periodic Single-Species Logistic System with Diffusion. (9th May 2013) - Yang, Chenxue; Ye, Mao; Liu, Zijian
Abstract : We study a single-species periodic logistic type dispersal system in a patchy environment with impulses. On the basis of inequality estimation technique, sufficient conditions of integrable form for the permanence and extinction of the system are obtained. By constructing an appropriate Lyapunov function, conditions for the existence of a unique globally attractively positive periodic solution are also established. Numerical examples are shown to verify the validity of our results and to further discuss the model.